PENGARUH ESG, RISK, KEPEMILIKAN INSTITUSIONAL, DAN CAPITAL TERHADAP KINERJA KEUANGAN PERBANKAN DI INDONESIA (Studi pada Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2020-2024) - Fabian Surjanto; Agus Purwanto (Diponegoro Journal of Accounting, 2026)
This research refers to previous studies that examine the determinants of financial performance in the banking sector, particularly the role of Environmental, Social, and Governance (ESG), risk management, ownership structure, and capital adequacy. This research aims to examine the effect of ESG, risk proxied by Non-Performing Loan (NPL) and Loan to Deposit Ratio (LDR), institutional ownership, and capital proxied by Capital Adequacy Ratio (CAR) on the financial performance of banking companies in Indonesia. The dependent variable used in this research is financial performance proxied by Return on Assets (ROA), while ESG, risk, institutional ownership, and capital are used as independent variables.Secondary data are used in this research and purposive sampling is employed as the sampling technique. The sample consists of banking companies listed on the Indonesia Stock Exchange during the period 2020–2024, resulting in 102 observations. The data are obtained from annual reports, financial reports, and Bloomberg ESG data. Panel data regression analysis is used to identify the effect of ESG, NPL, LDR, institutional ownership, and CAR on financial performance. The research results show that ESG, NPL, and institutional ownership do not have a significant effect on financial performance. Meanwhile, LDR has a significant negative effect on financial performance, and CAR has a significant positive effect on financial performance. These findings indicate that liquidity management and capital adequacy remain important determinants of banking financial performance in Indonesia, while ESG implementation and ownership structure have not yet shown a direct impact on profitability.